Reasons of early sexual debut of “female” adolescents attending Town-Two Clinic in Khayelitsha, South Africa - Spengane, Zandile (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.